New data on distribution of the wildcat (Felis silvestris Schreber, 1777) in Podillia, Ukraine - Drebet, M.; Kapeliukh, Ya. (Theriologia Ukrainica, 2019)
During 2016–2019, new data on the wildcat’s distribution in Khmelnytskyi, Vinnytsia, and Ternopil regions were obtained. The data concern 4 findings of the wildcat whereof 3 findings are dead specimens (a dead female in a poacher’s automatic trap, 2 specimens (male and female) hunted by a poacher, one specimen killed during the red fox population control measures in Podilski Tovtry National Nature Park, and one specimens recorded by a camera trap in Medobory Nature Reserve. The article provides detailed data on new findings of the species in Podillia and describes the environmental factors influencing its population, as well as provides recommendations on protection of the wildcat in the region. The frequency of occurrence of the wildcat in Podillia has been growing for several years. Nevertheless, the data remain incidental and occasional thus cannot indicate the growth of the species abundance in the region. Most of the located specimens were found dead on roads, in poacher traps or they were even killed during population control measures in the territory of protected areas. According to the information provided by Kamianets-Podilskyi organization of the Ukrainian Hunter and fishermen Society, its associate hunting teams annually obtain more than 100 specimens of feral cats, among which supposedly there is a great number of wildcats. Currently, spaying feral cats is the key element for preservation of the wildcat population in general, nevertheless, this aim remains unfulfilled only because this issue is not addressed properly thus a significant number of intact pets maintains contacts with the wildcat outside the human settlements. Ecological educational programs are an essential measure for the wildcat protection, especially in its habitats, though usually such work is aimed at both current and remote prospects. It is expected that a ban for hunting of feral cats in habitats of the wildcat implemented by including the appropriate paragraph into the population control permit issued by the Ecology and Natural Resources Department should enhance the species’ preservation in the near future. Availability of long-distance photographic equipment for locating the wildcat (such as camera traps) and monitoring system implementation at least on sites of protected areas would provide the required data on the abundance and distribution of the wildcat in the region allowing to improve measure for its protection and conservation. Впродовж 2016–2019 років отримано нові дані, щодо поширення кота лісового в межах Тернопільської, Хмельницької та Вінницької областей. Наводяться відомості про чотири сучасні знахідки кота лісового, з яких у трьох випадках йдеться про знахідки загиблих тварин (перший — загибель однієї особини, самки, у браконьєрському самолові, другий — браконьєрський відстріл двох особин, самець та самка, третій — відстріл однієї особини під час здійснення заходів з регулювання чисельності лиса рудого на території національного природного парку «Подільські Товтри»), у одному — про фіксацію однієї особини фотопасткою на території природного заповідника «Медобори». Здобуті відомості залишаються випадковими і не систематизованими. Основна частина виявлених тварин, це знахідки загиблих особин на автомобільних дорогах, у браконьєрських самоловах, та навіть вбиті тварини під час здійснення заходів з регулювання чисельності окремих видів тварин, в тому числі на територіях природно-заповідного фонду. За інформацією, поданою лише Кам’янець-Подільською РО УТМР, щороку, членами їх мисливських бригад добувається понад 100 особин здичавілих домашніх котів, серед яких, небезпідставно припускаємо, висока частка диких лісових котів. Стерилізація безпритульних домашніх котів є наразі найважливішою умовою збереження популяцій кота лісового, однак, зважаючи на те, що ніхто цим питанням серйозно не займається, вона не виконується, велика кількість нестерилізованих свійських котів продовжує контактувати з котом лісовим за межами населених пунктів. Еколого-освітні заходи є необхідною умовою охорони кота лісового, особливо у місцях його існування, однак, як правило, це робота на ближню і дальню перспективу. Заборона відстрілу здичавілих котів у місцях існування кота лісового сприятиме його збереженню вже у найближчому часі. Можливість використання дистанційних засобів фіксації кота лісового на фотопастки та запровадження системи моніторингу, хоча б на території ПЗФ, дасть змогу отримати необхідну інформацію щодо його чисельності та поширення в регіоні та можливість посилення його охорони та збереження.